Implementation Of Criminal Sanctions Against Crime Mining Potential Effects Without Permission For Deterrent Effect (Study On Jurisdiction Central Java Regional Police) - Nizar Anwar; Anis Mashdurohatun (Jurnal Daulat Hukum, 2019)
This study, entitled "Implementation of Criminal Sanctions Against Crime Mining Potential Effects Without Permission For Deterrent Effect (Study In Region Central Java Regional Police)". Based on the description in this thesis, that will be examined are: 1). How does the application of criminal sanctions against the crime of mining without a license in the jurisdiction of the Central Java Regional Police? 2). Is it true that criminal sanctions against mining without permission a criminal offense can be a deterrent effect? 3). How the barriers and solutions so the application of criminal sanctions against the crime of mining can be a deterrent effect?The study concluded that: 1). Penal provisions against the crimes mining unlicensed / illegal mining regulated in Act Number 4 of 2009 on Mineral and Coal, under Article 158, Article 160 Paragraph (1) and Paragraph (2), Article 161, Article 163 Paragraph ( 1) and Paragraph (2), and Article 164. 2). Act Mineral and Coal just set the maximum threat. This is impacting on the demands of the Public Prosecutor and the decision to be handed down by the judge. In the absence of a minimum penalty, the prosecutors and the judge may impose demands and the decision to a penalty is low, so it is feared not give deterrent effect to the perpetrators of illegal mining. 3). Mining Law there are four (4) weakness which some contradictory to each other, namely: a). In Article 169 (a) regarding the validity of the Contract of Work. b). Act Number 4 Of 2009 on Mineral and Coal Mining (Mining Law) are not set on the Mining Authority (KP). c). Mining Law regulates the obligation of business entities and IUPK IUP holders whose shares are owned by foreign investors to divest shares. d). Mining Law makes the shifting patterns of relationship between the government and mining entrepreneurs. Mining Law regulates the obligation of business entities and IUPK IUP holders whose shares are owned by foreign investors to divest shares. d). Mining Law makes the shifting patterns of relationship between the government and mining entrepreneurs. Mining Law regulates the obligation of business entities and IUPK IUP holders whose shares are owned by foreign investors to divest shares. d). Mining Law makes the shifting patterns of relationship between the government and mining entrepreneurs.Keywords: Sanctions; Criminal Act; Mining.